PRODUCTION AND PERFORMANCE OF OKARA/SAGO AND OKARA/BANANA PEEL ORGANIC FERTILIZERS IN PLANTATION - Lai, Josephine Chang Hui; Khairul Hafiz, Masrun; Nooralinah, Madinah; Rubiyah, Baini; Nur Amalina Shairah, Abdul Samat (Taylor’s University, 2021)
The application of chemical fertilizer improved the growth rate in the plantation. However, chemical fertilizer itself was not environmentally friendly. Thus, organic fertilizer with low production cost should be undergoing thorough research. This study investigated the performance of organic fertilizer produced using okara/sago and okara/banana peel on the growth rate of the plants. The organic fertilizers were produced into five samples with different ratios and placed in incubator oven at temperature 100ºC for 4 hours for drying process. Both organic fertilizers were analysed using FTIR, SEM and moisture balance analysis. Both fertilizers were then applied on and Mustard Looseleaf plants. FTIR and SEM analysis proved the well combination of okara with banana peel and sago with smoother surfaces, respectively. Both organic fertilizers were oven-dried to remain as solid stage. The results obtained proved that both organic fertilizers with the highest content of okara was the most effective in enhancing the growth rate of Mustard Looseleaf plants in terms of height and leaf size.